2018
DOI: 10.1016/j.nima.2018.09.075
|View full text |Cite
|
Sign up to set email alerts
|

A multi-cathode counter in a single-electron counting mode

Abstract: We describe a work of a multi-cathode counter of the developed design in a single electron counting mode with a cathode made of aluminum alloy. The results of the calibration of the counter are presented. The coefficient of gas amplification was found from the calibration spectra. The electric fields and operation of this detector in two configurations are described and the original idea to find the effect from electrons emitted from the surface of a cathode by difference of the rates measured in two volume co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…We have developed a special detector for this study-a multi-cathode counter [3]-and we have previously reported the first results of measurements using a counter with a copper cathode [4]. We have used a new counter of improved design, which employs an aluminium cathode and focusing rings, to make measurements with increased sensitivity [5]. Here we summarise the results of all of our measurements and outline our plans for further research.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a special detector for this study-a multi-cathode counter [3]-and we have previously reported the first results of measurements using a counter with a copper cathode [4]. We have used a new counter of improved design, which employs an aluminium cathode and focusing rings, to make measurements with increased sensitivity [5]. Here we summarise the results of all of our measurements and outline our plans for further research.…”
Section: Introductionmentioning
confidence: 99%
“…A schematic of the multi-cathode counter is shown in figure 1. The effect measured by this technique is determined by the difference R M CC of two count rates [1]: the one measured in the Configuration 1 when electrons emitted from a cathode of the counter reach a central wire (anode) 1) E-mail: beril@inr.ru of the counter and the other in the Configuration 2 when the electrons emitted from a cathode are scattered back by the locking negative potential of the second cathode near the first one. If we assume that the emission of the electron is the result of the conversion of a dark photon with mass (energy) m γ ′ , then the power that can be prescribed to this rate R M CC can be expressed as…”
Section: Methodsmentioning
confidence: 99%
“…So difference R MCC = R 1 -R 2 of the count rates in first and second configurations should give the net effect from single-electrons emitted from an external cathode. To find the efficiency of the counter for single-electron measurements the calibration has been performed by UV mercury vapor lamp through a quartz window in the side of the counter [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detector has been placed in a shielding cabinet at sea level. The single electron pulses with an average amplitude of about 9 mV have a Polya distribution [5].…”
Section: The Procedures Of Data Treatmentmentioning
confidence: 99%